Adipose-Derived Stem Cells in Crohn's Rectovaginal Fistula - García-Olmo, D. (Hindawi Publishing Corporation, 2010)
Therapeutic options for recto-vaginal fistula in the setting of Crohn's disease are limited and many data are available in the literature. The manuscript describes the history of a patient who has been the pioneer of our Clinical Trials in treating this disease in fistulizing Crohn's disease environment. We believe it is the first time that a patient with this disease has been treated by adipose-derived stem cells in allogeneic form. The conclusion of our study with Mary is that the use of mesenchymal stem cells derived from adipose tissue is secure, either in autologous or allogeneic form. Furthermore, we have proved that if we use multi-dose and multiple applications on a patient, it does not produce any adverse effect, which confirms us the safety of using these cells in patients at least in the fistulizing Crohn's disease environment.